Granulomatous Neutrophilic Cystic Mastitis, Case Report: Mastitis quística granulomatosa neutrofílica, Reporte de caso - Contreras Gala, Katherine Luisa (2020)
Cystic neutrophilic granulomatous mastitis (CNGM) is a recently characterized entity, with specific histopathological details that differentiate it from other types of chronic idiopathic mastitis. The presence of gram-positive bacilli within cystic-like spaces surrounded by neutrophils, in a context of suppurative granulomatous inflammation, define this entity. The importance of its recognition in the diagnostic report lies in its association with infection by corynebacterial species, so that treatment with antibiotics can be targeted, beyond the anti-inflammatory treatment that is usually administered to idiopathic mastitis.We describe the case of a 35-year-old female patient with no related history, with intermittent breast pain, associated with the presence of multiple hard, palpable nodules in both breasts, with results from multiple previous private biopsies that described chronic granulomatous mastitis with a tubercular reaction, for which she received treatment for tuberculosis. Despite this, the clinical response was partial. Histological slides were reviewed at the institution and the diagnosis of CNGM was then established.The presentation of this case was considered important due to its low recognition among pathologists, despite presenting characteristics already defined by previous studies.